2015
DOI: 10.2147/dddt.s78336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cationic polyamidoamine dendrimers’ dermal toxicity in the rat skin model

Abstract: Polyamidoamine (PAMAM) dendrimers are multi-branched, three-dimensional polymers with unique architecture, which makes these molecules attractive for medical and pharmaceutical applications. Using PAMAM as drug carriers for topical delivery might be beneficial as they only produce a transient effect without skin irritation. To evaluate the dermal toxicity of cationic PAMAM dendrimers generation 2 and generation 3, skin irritation studies were performed in vivo in the rat skin model. After 10 days topical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Some preparations cause a disruptor in the metabolism of keratinocytes and their abnormal keratosis, consisting of the separation of individual cells in the spinous layer, with formation of horn seeds and the formation of so-called round cells44 that we also observed in our study. This may confirm the results of Winnicka’s research, in which she observed that the morphological changes of epidermal cells of rats treated with PAMAM dendrimers included cytoplasmic vacuolization of keratinocytes in the basal and spinous layers 17…”
Section: Discussionsupporting
confidence: 88%
“…Some preparations cause a disruptor in the metabolism of keratinocytes and their abnormal keratosis, consisting of the separation of individual cells in the spinous layer, with formation of horn seeds and the formation of so-called round cells44 that we also observed in our study. This may confirm the results of Winnicka’s research, in which she observed that the morphological changes of epidermal cells of rats treated with PAMAM dendrimers included cytoplasmic vacuolization of keratinocytes in the basal and spinous layers 17…”
Section: Discussionsupporting
confidence: 88%
“…It can be divided in 2 main directions, the first being where dendrimers are used to improve the action of antibodies [36,37] or multivalent antibody-antigen interactions [40,41], to present new kinds of adjuvants [42][43][44], to improve visualization of proteins [45,46], to construct dendrimerconjugated peptide vaccines [47,48] and dendrimer-antibody complex systems for siRNA or drug delivery [49][50][51]. In second direction, immunoreactivity of proteins as well as the interaction of dendrimers with antibodies are examined as a side effect of possible application of dendrimers [52][53][54][55][56]. In particular, Wangler et al [53] showed that in antibody-dendrimer conjugates, the number, but not the size of the dendrimers, determines the immunoreactivity of these complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were passed through series of alcohol for dehydration (70%, 90% and 100%) and examined using a light microscope Olympus BX41 (Olympus Corporation, Tokyo, Japan) at 200× magnifications interfaced with an image analysis system. The images were captured using a DP12 camera (Olympus Corporation, Tokyo, Japan) [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%